The Implementation of Digital Governance in Indonesia:A Systematic Review of Challenges and Opportunities - Lalu Ahmad Murdhani (Yayasan Hisnul Muslim Lombok, 2025)
The implementation of digital governance in Indonesia is a strategic step towards achieving more efficient, transparent, and participatory government management through the use of digital technology. This study aims to analyze the challenges and opportunities Indonesia faces in the process of government digitalization using the Systematic Literature Review (SLR) method on various relevant literature. The results show that the implementation of digital governance in Indonesia has made significant progress, marked by regulations such as Presidential Regulation No. 95 of 2018 on the Electronic-Based Government System (SPBE) and various public service digitalization initiatives. However, the challenges faced include limited digital infrastructure, low digital literacy among the public, cybersecurity threats, and unequal human resource capacities across government institutions. On the other hand, the opportunities that can be leveraged include the increasingly widespread development of digital infrastructure, the enhancement of digital literacy through various training programs, collaboration between the government, private sector, and civil society, as well as the utilization of cutting-edge technologies such as Artificial Intelligence, Big Data, and Blockchain to support government transparency and efficiency. This study highlights the importance of strengthening regulations, enhancing human resource capacities, integrating systems comprehensively, and fortifying cybersecurity to support the success of digital governance in Indonesia. By addressing the challenges and seizing the available opportunities, government digitalization in Indonesia has the potential to create more adaptive, transparent, and inclusive governance in the digital era.